Incidence of Contrast-Induced Nephropathy in Post-Renal Transplant Recipients: Contrast-Induced Nephropathy in Post-Renal Transplant Recipients - Naseer, Amara; Ahmed, Ejaz; Anmol, .; Kumari, Anusha (Pakistan Journal of Health Sciences, 2026)
Contrast-induced nephropathy (CIN) is a widely occurring, although possibly preventable, complication after the use of iodinated contrast media. Objectives: To identify CIN incidence in patients who have undergone renal transplants and also to see the risk factors involved. Methods: The cross-sectional research was carried out at the Sindh Institute of Urology and Transplantation (SIUT), Karachi, within six months after ethical consent of the College of Physicians and Surgeons Pakistan (CPSP). The sample size was 174 renal transplant recipients (aged 18 years and above) with an estimated glomerular filtration rate (eGFR) of over 20 ml/min, and these individuals were pre-exposed to 50 ml of iodinated contrast. Data analysis was done by use of SPSS version 25.0. Associations were evaluated using the chi-square test and multivariate logistic regression, with p≤0.005 being taken as statistically significant. Results: The average age of the interviewees was 44.2 ± 11.6 years old. The mean serum creatinine increased to 1.76 ± 0.49 mg/dl at the end of the experiment and correspondingly decreased to 55.6 ± 12.3 ml/min to 49.8 ± 13.1 ml/min. CIN appeared in 26 patients (14.9%). Its occurrence was much higher among those patients who had diabetes mellitus (23.8%, p=0.021) and hypertension (19.2%, p=0.045). On multivariate analysis, independent predictors of CIN were diabetes mellitus and contrast volume more than 100 ml (p<0.001). Conclusions: CIN is very prevalent among the post-renal transplant recipients. Higher contrast volume and diabetes mellitus are the best independent predictors.